Effect of Mg-Gluconate on the Osmotic Fragility of Red Blood Cells, Lipid Peroxidation, and Ca2+-ATPase (PMCA) Activity of Placental Homogenates and Red Blood Cell Ghosts From Salt-Loaded Pregnant Rats - Rojas, Deliana; Abad, Cilia; Piñero, Sandy; Medina, Yollyseth; Chiarello, Delia I.; Proverbio, Fulgencio; Marín, Reinaldo (Frontiers in Physiology, 2022)
Preeclampsia (PE) is a pregnancy-specific syndrome with multisystem involvement which leads to fetal, neonatal, and maternal morbidity and mortality. A model of salt-loaded pregnant rats has been previously studied, sharing several pathological characteristics of preeclamptic women. In this study, it was compared the effects of the treatment with an oral magnesium salt, magnesium gluconate (Mg-gluconate), on the osmotic fragility of red blood cells, lipid peroxidation, and PMCA activity of placental homogenates and red blood cell ghosts in salt-loaded pregnant rats Mg-gluconate has a higher antioxidant capacity than MgSO4 due to the presence of several hydroxyl groups in the two anions of this salt. Salt-loaded pregnant rats received 1.8% NaCl solution ad libitum as a beverage during the last week of pregnancy. On day 22nd of pregnancy, the rats were euthanized and red blood cells and placenta were obtained. Salt-loaded pregnant rats showed an increased level of lipid peroxidation and a lowered PMCA activity in placental and red blood cell ghosts, as well as an increased osmotic fragility of their red blood cells. The treatment of the salt-loaded pregnant rats with Mg-gluconate avoids the rise in the level of lipid peroxidation and the concomitant lowering of the PMCA activity of their red blood cell membranes, reaching values similar to those from control pregnant rats. Also, this treatment prevents the increase of the osmotic fragility of their red blood cells, keeping values similar to those from control pregnant rats. Mg-gluconate seems to be an important candidate for the replacement of the MgSO4 treatment of preeclamptic women.